2012
DOI: 10.1111/nph.12006
|View full text |Cite
|
Sign up to set email alerts
|

Eliminating the purple acid phosphatase AtPAP26 in Arabidopsis thaliana delays leaf senescence and impairs phosphorus remobilization

Abstract: SummaryLimitation of crop productivity by suboptimal phosphorus (P) nutrition is a widespread concern. Enhanced crop P-use efficiency could be achieved by improving P remobilization from senescing leaves to developing tissues and seeds. Transcriptomic studies indicate that hundreds of Arabidopsis thaliana genes are up-regulated during leaf senescence, including that encoding the purple acid phosphatase (PAP) AtPAP26 (At5g34850).In this study, biochemical and functional genomic tools were integrated to test the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
104
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(106 citation statements)
references
References 27 publications
(65 reference statements)
1
104
0
1
Order By: Relevance
“…Purple acid phosphatase (PAP) family members were involved in extensive aspects of plant development, mineral homeostasis and stress responses (González-Muñoz et al, 2015). In Arabidopsis thaliana , the elimination of AtPAP26 disturbed phosphorus remobilization and delayed leaf senescence (Robinson et al, 2012). In the current study, heat stress and combined stress down-regulated PAP expression.…”
Section: Discussionmentioning
confidence: 99%
“…Purple acid phosphatase (PAP) family members were involved in extensive aspects of plant development, mineral homeostasis and stress responses (González-Muñoz et al, 2015). In Arabidopsis thaliana , the elimination of AtPAP26 disturbed phosphorus remobilization and delayed leaf senescence (Robinson et al, 2012). In the current study, heat stress and combined stress down-regulated PAP expression.…”
Section: Discussionmentioning
confidence: 99%
“…A second line of enquiry using lpa mutants or transgenic plants with altered phosphatase scavenging capacity has also suggested that alterations to seed P affect seed germination and seedling vigor (Raboy, 2009; Robinson et al, 2012). Studies with lpa mutants across a range of species found reduced seedling vigor or impaired germination compared to wild-type parent lines (Meis et al, 2003; Kim and Tai, 2011).…”
Section: Phosphorus Effects On Seed Germination and Seedling Vigormentioning
confidence: 99%
“…In the early phase of leaf senescence, developmental and environmental cues signal the plant cells to activate transcription factors (TFs) that modulate the expression of senescence-associated genes (SAGs) (Guo and Ecker, 2004; Balazadeh et al , 2008). The products of these SAGs conduct the highly ordered breakdown of intracellular organelles, including the degradation of proteins and macromolecules to remobilize leaf nutrients into other developing organs such as new leaves or seeds, or into storage organs (Lim et al , 2007; Robinson et al , 2012). …”
Section: Introductionmentioning
confidence: 99%